2018
DOI: 10.1111/cen.13580
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and body composition in children with congenital adrenal hyperplasia

Abstract: Lower BMD was observed in CAH cases compared with controls although no differences in body composition were identified. Among CAH cases, increased chronic androgen exposure, as measured by bone age Z-scores, was associated with higher BMD but was not associated with VAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…Most studies on adults and children with CAH have reported an increased BMI (6, 89, 124, 125, 128, 129, 130, , 131, 132, 133, 134, 135, 136, 137, 138), but not all (4,73,94,139,140,141,142). The frequency of obesity did not differ between patients with NCAH and classic CAH in some studies (6,94,122,124,125,143), while others reported a lower BMI in patients with NCAH (89).…”
Section: Obesitymentioning
confidence: 93%
“…Most studies on adults and children with CAH have reported an increased BMI (6, 89, 124, 125, 128, 129, 130, , 131, 132, 133, 134, 135, 136, 137, 138), but not all (4,73,94,139,140,141,142). The frequency of obesity did not differ between patients with NCAH and classic CAH in some studies (6,94,122,124,125,143), while others reported a lower BMI in patients with NCAH (89).…”
Section: Obesitymentioning
confidence: 93%
“…Whether the increased prevalence of obesity results from an increased lean body mass (as a possible consequence of excess androgens) or total/regional fat mass has been explored through bioimpedance analysis (11, 26, 27), dual x-ray absorptiometry (DEXA) (12, 15, 2832), and computer tomography (CT) imaging (33) (Table 1). Several studies relying on DEXA documented that either males or females with classic CAH exhibit higher total fat mass (12, 15, 2830) and reduced lean body mass (29) than controls.…”
Section: Traditional CV Risk Factorsmentioning
confidence: 99%
“…Only a few data are available regarding NC CAH (27, 28, 32), documenting no significant differences between classic and NC forms. Interestingly, one study reported a higher lean body mass in NC CAH in comparison to matched controls, suggesting an effect of longer exposure to excess androgens (28).…”
Section: Traditional CV Risk Factorsmentioning
confidence: 99%
“…Moreover, a higher prevalence of obesity, impaired glucose tolerance, and dyslipidemia has been demonstrated in patients with Addison's disease [ 39 ], with increased use of antihypertensive drugs and lipid-lowering agents, as well as an increased risk for cardiovascular morbidity compared to general population [ 40 ]. Children with CAH, on supraphysiological glucocorticoid doses that cause an altered diurnal cortisol profile, have high rate of obesity, hypertension, growth suppression, and low bone density [ 41 43 ]. Increased evening cortisol levels have been shown to reduce glucose tolerance, insulin secretion, and insulin sensitivity in healthy young adults [ 44 ].…”
Section: Treatment Of Aimentioning
confidence: 99%